The effectiveness of group reminiscence therapy for loneliness, anxiety and depression in older adults in long-term care: a systematic review - Syed Elias, Sharifah Munirah; Neville, Christine; Scott, Theresa (Elsevier, 2015)
Loneliness, anxiety and depression are common problems for older adults in long-term care. Reminiscence therapy is a non-pharmacological intervention that may be of some benefit. In comparison to individual reminiscence therapy, group reminiscence therapy is a preferred option when dealing with the resource constraints of long-term care. The aim of this paper was to systematically review the literature in order to explore the effectiveness of group reminiscence therapy for older adults with loneliness, anxiety and depression in long-term care. Results indicated that group reminiscence therapy is an effective treatment for depression in older adults, however to date, there is limited research support for its effectiveness to treat loneliness and anxiety. Further research and an improvement in methodological quality, such as using qualitative and mixed methods approaches, is recommended to help establish an evidence base and provide better understanding of the effectiveness of group reminiscence therapy.